2018
DOI: 10.1038/s41371-018-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

The risk of metabolic syndrome as a result of lifestyle among Ellisras rural young adults

Abstract: The study aimed to investigate the association between metabolic syndrome (MetS) and lifestyle risk factors among Ellisras adults. A cross-sectional study was conducted on 624 adults (306 males and 318 females). MetS was defined according to the criteria of the International Diabetes Federation. The prevalence of MetS was 23.1% (8.6% males and 36.8 % females). Females appeared to have higher mean values for waist circumference (WC), fasting blood glucose (FBG), total cholesterol (TCHOL) and low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…35 In fact, WC and HDL-C levels are the most important risk factors that explain the higher susceptibility of women compared to men. 36 Hajian-Tilaki et al also reported that obesity was significantly higher in females. 37 According to the results of our study, elevated triglyceride was the second most prevalent component of MetS after obesity.…”
Section: Discussionmentioning
confidence: 95%
“…35 In fact, WC and HDL-C levels are the most important risk factors that explain the higher susceptibility of women compared to men. 36 Hajian-Tilaki et al also reported that obesity was significantly higher in females. 37 According to the results of our study, elevated triglyceride was the second most prevalent component of MetS after obesity.…”
Section: Discussionmentioning
confidence: 95%
“…In our present study, the prevalence of decreased HDL-C levels also increased significantly, from 21.21% to 36.73% ( p = 0.016), in the subgroups aged 20–34 years, while there was no significant change in the other age groups between 2006 and 2018. High prevalence of MetS was also detected among young adults (aged 18–30 years) in a study recently published [ 39 ] on the Ellisras (town in the Limpopo province of South Africa) rural population, and increasing prevalence of MetS even among children and adolescents seems to be a worldwide phenomenon [ 40 , 41 , 42 ]. These observations are interpreted as outcomes of severe nutritional changes and missing preventive interventions targeting healthy diet [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is said that the prevalence of metabolic syndrome in young adults has increased in the last 15 years 8 . This can be caused by Westernized diet, sedentary lifestyle, excessive alcohol intake, and smoking at productive age 9 . However, early detection of metabolic syndrome in young adults can provide more effective prevention because of cost-saving and reducing disability-adjusted life years 10 .…”
Section: Discussionmentioning
confidence: 99%